Determination of Sun Protection Factor (SPF) number of some aqueous herbal extracts - C. Malsawmtluangi, Deepak Kumar Nath, Italini Jamatia, Lianhimgthangi, E. Zarzoliana, Lalduhsanga Pachuau (Journal of Applied Pharmaceutical Science, 2013)
The aim of the present study was to determine the ultraviolet (UV) absorption properties of aqueous herbal extracts of some commonly found vegetable sources by determining the sun protection factor (SPF) number. The in vitro SPF number is determined according to the spectrophotometric method described by Mansur et al. Aqueous herbal extracts were prepared and after dilution with alcoholic solutions the absorbance were recorded between 290-320 nm using UV-vis spectrophotometry. It was observed that all of the tested herbals showed some UV protection capabilities with aqueous coconut extract showing the highest SPF number of 7.38 while watermelon showed the lowest SPF number of 0.97.
Keywords: UV absorption, Sun Protection Factor (SPF), sunscree